Fostering aspects of religion, education, and skills for adolescents in Tebas Sungai Sambas Regency - Mushoddik, M.; Amirullah, Gufron; Susilo, S. (Universitas Muhammadiyah Malang, 2021)
Youth development is seen as a form of skill to improve the quality of youth or youth groups which is most appropriate because apart from opening the knowledge and abilities of talents that must be known as the next generation to build urban areas so they know very well the problems they are facing and the conditions to be achieved. The community service program aims to build capacity in 3 groups for aspects of Religion, Education and Skills. The training material prepared is based on an analysis of the participants' needs which is carried out through socialization and training with the attendance of 30 participants. Participants consisted of various hamlet heads, youth and youth organizations around the hamlet. The approach method used in community service is training and socialization. Community service activities (Thematic KKN) have been carried out well. Activities began with data collection and mapping, drafting a work program, and implementing activities in Tebas Sungai Village. The core activities that will be carried out include (1) religious guidance; (2) education fostering; and (3) Skills development. To ensure the sustainability of the activity, suggestions, involvement and enthusiasm of the residents of Tebas Sungai Village are highly expected so that this village becomes a Pilot village for the surrounding villages.